1993
DOI: 10.1007/bf01229528
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of miltefosine alone and after combination with platinum complexes on MXT mouse mammary carcinoma models

Abstract: Summary.Miltefosine, an alkylphosphocholine structurally related to alkyllysophospholipids showed highly selective antitumour activity against the hormone-sensitive variant of the s.c. transplantable MXT mouse mammary adenocarcinoma, the ovary-dependent MXT (M3.2), whereas it was inactive against the hormone-insensitive MXT (M3.2) OVEX variant. A dose of 32 mg/kg miltefosine p.o. daily for 5 weeks was well tolerated. Histopathological evaluation gave no signs of gastroenteral toxicity. After therapy the microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Nevertheless, despite not achieving the primary objectives related to significant increases in progression-free survival rates, some optimism still remained for this agent in advanced soft tissue sarcoma patients (Bailey, et al, 2006), as well as to warrant further evaluation of perifosine in combination with rituximab or other active agents in patients with relapsed/refractory Waldenstrom's macroglobulinemia (Ghobrial, et al, 2010), and with currently available therapies in renal cancer (Cho, et al, 2012). Furthermore, a number of studies have reported the potentiation of antitumor activity following combination of perifosine with distinct anticancer drugs in cancer cells derived from several types of leukemia (Nyakern, et al, 2006;Papa, et al, 2008;Tazzari, et al, 2008), multiple myeloma Hideshima, et al, 2006), osteosarcoma (Yao, et al, 2013), medulloblastoma (Kumar, et al, 2009), lung cancer (Elrod, et al, 2007), colon cancer (M. B. Chen, et al, 2012, and glioma (Momota, et al, 2005), as well as following combination of miltefosine with different anticancer compounds or treatments in distinct cancer cell types (Haberkorn, et al, 1992;Papagiannaros, et al, 2006;Spruss, et al, 1993;Thakur, et al, 2013). Thus, phase II clinical trials were conducted with…”
Section: Alkylphosphocholinesmentioning
confidence: 96%
“…Nevertheless, despite not achieving the primary objectives related to significant increases in progression-free survival rates, some optimism still remained for this agent in advanced soft tissue sarcoma patients (Bailey, et al, 2006), as well as to warrant further evaluation of perifosine in combination with rituximab or other active agents in patients with relapsed/refractory Waldenstrom's macroglobulinemia (Ghobrial, et al, 2010), and with currently available therapies in renal cancer (Cho, et al, 2012). Furthermore, a number of studies have reported the potentiation of antitumor activity following combination of perifosine with distinct anticancer drugs in cancer cells derived from several types of leukemia (Nyakern, et al, 2006;Papa, et al, 2008;Tazzari, et al, 2008), multiple myeloma Hideshima, et al, 2006), osteosarcoma (Yao, et al, 2013), medulloblastoma (Kumar, et al, 2009), lung cancer (Elrod, et al, 2007), colon cancer (M. B. Chen, et al, 2012, and glioma (Momota, et al, 2005), as well as following combination of miltefosine with different anticancer compounds or treatments in distinct cancer cell types (Haberkorn, et al, 1992;Papagiannaros, et al, 2006;Spruss, et al, 1993;Thakur, et al, 2013). Thus, phase II clinical trials were conducted with…”
Section: Alkylphosphocholinesmentioning
confidence: 96%
“…For this objective, drug repurposing is an excellent alternative to finding new treatments since these drugs already approved to be used in humans and animals, initially developed to treat other diseases, can help treat infections caused by different pathogens (59,60). Such is the case of commercial MFS, which was initially used as an antineoplastic drug (27,28) that is now the only available oral treatment for leishmaniasis in dogs and humans (29)(30)(31)(32), and was recently proven to be effective for the treatment of infections caused by Candida species (39,40). As previously demonstrated (45,46,48), MFS also has in vitro fungicidal activity against Sporothrix species by inhibiting the growth of both fungal morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…For this objective, drug repurposing is an excellent alternative to finding new treatments since these drugs already approved to be used in humans and animals, initially developed to treat other diseases, can help treat infections caused by different pathogens (59,60). Such is the case of commercial MFS, which was initially used as an antineoplastic drug (27,28) that is now the only . CC-BY-NC-ND 4.0 International license perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations